Responses of endogenous proline in rice seedlings under chromium exposure - X.Z. Yu; M.R. Lu (Global Journal of Environmental Science and Management)
Hydroponic experiments were performed to exam the dynamic change of endogenous proline in rice seedlings exposed to potassium chromate chromium (VI) or chromium nitrate chromium (III). Although accumulation of both chromium species in rice seedlings was obvious, more chromium was detected in plant tissues of rice seedlings exposed to chromium (III) than those in chromium (VI), majority being in roots rather than shoots. Results also showed that the accumulation capacity of chromium by rice seedlings was positively correlated to chromium concentrations supplied in both chromium variants and the accumulation curve depicted an exponential trend in both chromium treatments over the entire period of exposure. Proline assays showed that both chromium variants induced the change of endogenous proline in shoots and roots of rice seedlings. Chromium (VI) of 12.8 mg/L increased proline content significantly (p